Explanation of Phonemic Predominance in the Arabic Language - Alfugara, Saif aldain; Al-Suhaimat, Bayan Ahmad (Dirasat: Human and Social Sciences, 2023)
Objectives: The research addresses the prevalence of the predominance problem in Arabic language lessons, highlighting a lack of specialized studies on its dimensions and role in linguistic analysis. It aims to explore the dominance of the phonetic level in Arabic, define the concept, present scholars’ viewpoints, distinguish it from preponderance, and identify manifestations in sounds like tilting, vocalism, and substitution. Methods: The study relied on the descriptive analytical method by collecting the manifestations of the predominance of sounds identified by scholars in linguistic sources, classifying them in issues, and analyzing them to know the role of this issue in the interpretation of its use from a phonetic perspective. Results: The study showed that predominance is a linguistic issue that means dominance and is different from the phenomenon of preponderance, and scholars relied on it in explaining the linguistic uses and justifying its current state. This issue was of two types: a usage reason based on commonality, i.e., predominance in frequent use, and an investigational linguistic cause which means the power and control of one linguistic element over the other elements. This issue was common in linguistic sources with slight differences between them. It extensively emerged after the fourth century AH and had phonetic, morphological, and syntactic forms. Conclusion: This issue contradicts the phenomenon of preponderance, and it appeared in the linguistic lesson after the fourth century AH where it had its own issues. The scholars explained linguistic issues in sounds, morphology, and grammar using it.